Effect of Poly(trehalose methacrylate) Molecular Weight and Concentration on the Stability and Viscosity of Insulin. Issue 9 (22nd May 2021) - Gelb, Madeline B.; Maynard, Heather D.
Abstract: Instability to storage and shipping conditions and injection administration remain major challenges in treating chronic conditions with biopharmaceuticals. Herein, formulations of poly(trehalose methacrylate) (pTrMA) are successfully optimized to stabilize insulin without appreciably increasing viscosity. Polymers are synthesized (2400–29 200 Da), and added to insulin at different concentrations. pTrMA maintained >95% intact insulin against 250 rpm at 37 °C for 3 h with at least 10 mol. equiv. of 5.0 kDa, 7.5 mol. equiv. of 9.4 kDa, 5 mol. equiv. of 12.8 kDa, 1 mol. equiv. of 19.8 kDa, and 0.5 mol. equiv. of 29.2 kDa polymers, compared to 13.1% of insulin alone. The lowest pTrMA concentration formulations are more viscous than insulin alone, but the highest viscosity, U‐600 with 10 mol. equiv. of 5 kDa pTrMA, is only 1.43 cP at 25 °C. This data demonstrates that pTrMA is a promising low viscosity additive to stabilize the diabetes therapeutic insulin. Abstract : This manuscript details formulation optimization of a trehalose polymer (pTrMA) to stabilize insulin to heat and agitation. Increasing pTrMA equivalents and molecular weight increases the amount of intact insulin after stress. pTrMA has Newtonian fluid behavior and does not increase the viscosity of insulin above known safety thresholds. This work demonstrates that pTrMA is suitable for the formulation of insulin.